Hepatocellular Carcinoma: Cause of Diaphragmatic Herniation in Canine - Kumar, Sarvan; Tiwari, Vipin; Sakshi,; Choudhary, Anju; Mandal, Kruti D. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Diaphragmatic hernia (DH) may be congenital or acquired. Most diaphragmatic defects reported in bovines are either  traumatic in origin or have a history of advanced pregnancy  or recent calving (Smith, 2002). DH may also occur as a  result of progressive weakening of the diaphragm adjacent  to a hardware perforation and reticuloperitonitis (Divers  and Peek, 2008). There is meager literature on congenital  diaphragmatic defects in horses and accidental, spontaneous  rupture usually occurs from abdominal crushing, following  blunt trauma or penetrating injuries to the abdomen and  chest (Sasho and Dian, 2009). Cases of DH in canine are less  frequently noticed. There is the occasional report of DH  in canines due to a neoplastic growth like hepatocellular  carcinoma. This communication reports a case of Rottweiler  pup, which was presented with clinical signs of dyspnea  and vomiting, that was tentative diagnosed as respiratory  pathology and was subjected to further investigation and  autopsy.
Keywords: Hepatocellular Carcinoma; Diaphragmatic Herniation; Canine